2006
DOI: 10.1007/s11104-006-9164-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-applied sodium chloride promotes cadmium accumulation in durum wheat grain

Abstract: Cadmium (Cd) accumulation in durum wheat grain is a growing concern. Among the factors affecting Cd accumulation in plants, soil chloride (Cl) concentration plays a critical role. The effect of leaf NaCl application on grain Cd was studied in greenhouse-grown durum wheat (Triticum turgidum L. durum, cv. Balcali-2000) by immersing (10 s) intact flag leaves into Cd and/or NaCl-containing solutions for 14 times during heading and dough stages. Immersing flag leaves in solutions containing increasing amount of Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…Cl is an essential element for plants, as it acts as a major osmotically active solute in the vacuole and it is involved in both turgor and osmoregulation (White and Broadley 2001). Moreover, the complexation of Cl with heavy metals for example Cd, was reported to reduce the positive charge of the metal ions (Ozkutlu et al 2007). On the other hand, while it is known that in hyperaccumulators metals are predominantly bound by weak oxygen/nitrogen ligands, sulphur ligands represent approximately 30 % Cd in mature leaves of N. caerulescens and 20 % in the epidermis of mature leaves of N. praecox (Küpper et al 2004;Vogel-Mikuš et al 2010).…”
Section: Hyperaccumulation Of CD and Zn By S Plumbizincicolamentioning
confidence: 99%
“…Cl is an essential element for plants, as it acts as a major osmotically active solute in the vacuole and it is involved in both turgor and osmoregulation (White and Broadley 2001). Moreover, the complexation of Cl with heavy metals for example Cd, was reported to reduce the positive charge of the metal ions (Ozkutlu et al 2007). On the other hand, while it is known that in hyperaccumulators metals are predominantly bound by weak oxygen/nitrogen ligands, sulphur ligands represent approximately 30 % Cd in mature leaves of N. caerulescens and 20 % in the epidermis of mature leaves of N. praecox (Küpper et al 2004;Vogel-Mikuš et al 2010).…”
Section: Hyperaccumulation Of CD and Zn By S Plumbizincicolamentioning
confidence: 99%
“…Many researchers have suggested that this phenomenon explains the increasing Cd concentration in crops grown in fields rich in Cl. In contrast, Ozkutlu et al (2007) showed that leaf-applied sodium chloride promotes Cd accumulation in durum wheat grain. In the present study, the application of NH 4 Cl fertilizer increased Cl concentrations in both the soil and wheat straw, with grain Cd concentration being correlated with both soil and straw Cl concentrations.…”
Section: Discussionmentioning
confidence: 91%
“…The CdCl 2 was probably dissociated already in the nutrient solution under the given conditions, and in the plant tissues the Cl did not co-precipitate back with Cd. CdCl 2 therefore does not have a role in facilitating Cd uptake and transport in N. praecox through the mechanisms of charge reduction or removal (i.e., the CdCl 2 0 species), which increase the diffusivity/lipophilicity of Cd and enhances its ability to penetrate through membranes, as proposed by Ozkutlu et al (2007), but more likely has a role in Cd vacuolar sequestration through activation of V-ATP-ases by chloride (Broadley et al 2012).…”
Section: CD S Cl and P Accumulation And The Cd Ligand Environmentmentioning
confidence: 97%
“…In the plant-cell cytoplasm, Cl − regulates the activities of enzymes and acts as a counter anion, with Cl − fluxes implicated in stabilisation of the membrane potential, and regulation of pH gradients and electrical excitability (White and Broadley 2001). Chloride applied to leaves in the form of NaCl was shown to promote Cd accumulation in durum wheat grain, which was attributed to the Cl − complexing of Cd and thus to a reduction in the positive charge on the metal ion (Ozkutlu et al 2007). Charge reduction or removal (e.g., CdCl 2 0 species) increases the diffusivity/lipophilicity of Cd and enhances its penetration through the membranes of leaf epidermal cells (Ozkutlu et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation